2022
DOI: 10.3390/metabo13010050
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Combined Effects of Probiotics and Prebiotics as Supplements or Food-Rich Diets on a Propionic-Acid-Induced Rodent Model of Autism Spectrum Disorder

Abstract: The link between nutrition and autism spectrum disorder (ASD) as a neurodevelopmental condition, which is clinically presented as significant delays or deviations in interaction and communication, has provided a fresh point of view and signals that nutrition may play a role in the etiology of ASD, as well as playing an effective role in treatment by improving symptoms. In this study, 36 male albino rat pups were used. They were randomly divided into five groups. The control group was fed only a standard diet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…While existing pharmaceuticals like risperidone and aripiprazole have been approved by FDA to relieve ASD symptoms, they do not address the core symptoms of the condition and may actually exacerbate them (King et al, 2009; McPheeters et al, 2011). Luteolin (50 mg/kg) supplementation was effective in mitigating PPA‐induced ASD features in rats (Alsubaiei et al, 2022) and improving social impairments in children with ASD at a dose of 100 mg/capsule (Taliou et al, 2013). In this context, our results showed that lotusine (10 mg/kg) effectively ameliorated social deficits in the PPA mouse, further highlighting its potential as a nutritional supplement to relieve ASD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While existing pharmaceuticals like risperidone and aripiprazole have been approved by FDA to relieve ASD symptoms, they do not address the core symptoms of the condition and may actually exacerbate them (King et al, 2009; McPheeters et al, 2011). Luteolin (50 mg/kg) supplementation was effective in mitigating PPA‐induced ASD features in rats (Alsubaiei et al, 2022) and improving social impairments in children with ASD at a dose of 100 mg/capsule (Taliou et al, 2013). In this context, our results showed that lotusine (10 mg/kg) effectively ameliorated social deficits in the PPA mouse, further highlighting its potential as a nutritional supplement to relieve ASD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Nelumbinis Plumula is a medicine‐food homology plant widely used in traditional Chinese medicine. Its active compounds have demonstrated significant potential in alleviating ASD symptoms, such as improving eye contact, enhancing social interaction, and addressing sleep disorders (Alsubaiei et al, 2022; Theoharides et al, 2012; Zambrelli et al, 2021). Lotusine, as a main active ingredient of Nelumbinis Plumula , is a natural alkaloid known for its antioxidant (Harishkumar & Selvaraj, 2020), antihypertensive (Zhan et al, 2023), and cardiovascular properties (Harishkumar & Selvaraj, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The control group received only phosphate buffer and was fed a standard diet; the PPA group received a neurotoxic dose of PPA (250 mg/kg body weight) [37] for the first three consecutive days and was put on a standard diet. The PPA + S. Empero group was administered the same dose of PPA and put on a standard diet mixed with Lethrinus nebuloses fish for 36 days.…”
Section: Experimental Design 231 Animalsmentioning
confidence: 99%